2004
DOI: 10.1159/000083658
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Pituitary Vasoactive Intestinal Peptide in Dopaminergic Inhibition of Estrogen-Induced Pituitary Hyperplasia and Vascular Endothelial Growth Factor Expression

Abstract: We have shown that pituitary vasoactive intestinal peptide (VIP) mediates the effects of estrogen on lactotrope hyperplasia, angiogenesis and hyperprolactinemia, and reduces the pituitary content of transforming growth factor beta β1 (TGF-β1, an inhibitor of lactotrope proliferation). Dopamine agonists reverse lactotrope hyperplasia and hyperprolactinemia and also reduce the pituitary VIP content in hyperestrogenized rats. To elucidate the interaction of bromocriptine (BC) and pituitary VIP, a VIP receptor ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…These data suggest that pituitary VIP mediates the effect of E on lactotrope hyperplasia, pituitary TGF-b1, and angiogenesis [32]. It has been also shown that E in vitro enhances and bromocriptine reduces not only expression and release of VIP in anterior pituitary cell culture, but the endothelial growth factor as well [33]. Diagrams showing the effect of sexual steroid treatments on the basal PRL levels in various experimental groups.…”
Section: Discussionmentioning
confidence: 87%
“…These data suggest that pituitary VIP mediates the effect of E on lactotrope hyperplasia, pituitary TGF-b1, and angiogenesis [32]. It has been also shown that E in vitro enhances and bromocriptine reduces not only expression and release of VIP in anterior pituitary cell culture, but the endothelial growth factor as well [33]. Diagrams showing the effect of sexual steroid treatments on the basal PRL levels in various experimental groups.…”
Section: Discussionmentioning
confidence: 87%
“…This is the first report that the TH polymorphism is associated with risk of GC. Previous studies have shown that DA strongly and selectively inhibits the expression of vascular permeability factor/vascular endothelial growth factor (VPF/VEGF) [20][21][22], which promote the growth and progression of GC. Therefore, it is possible that TH contributes to the susceptibility to GC by regulating the expression of DA.…”
Section: Discussionmentioning
confidence: 99%
“…205). VIP is also produced by the lactotrophs, where it maintains elevated basal PRL release (206). VIP acts by increasing intracellular cAMP, followed by PKA activation.…”
Section: Prl Releasing/regulating Factorsmentioning
confidence: 99%